Learning from the machine: interpreting machine learning algorithms for point- and extended-source classification. Issue 3 (20th September 2018) - Morice-Atkinson, Xan; Hoyle, Ben; Bacon, David
ABSTRACT: We investigate star-galaxy classification for astronomical surveys in the context of four methods enabling the interpretation of black-box machine learning systems. The first explores the decision boundaries as given by decision tree based methods, enabling the visualization of the classification categories. Secondly, we investigate how the Mutual Information based Transductive Feature Selection (MINT) algorithm can be used to perform feature preselection. If a small number of input features is required for the machine learning classification algorithm, feature preselection provides a method to determine which of the many possible input features should be selected. Third is the use of the tree-interpreter package to enable popular decision tree based ensemble methods to be opened, visualized, and understood. This is done by additional analysis of the tree-based model, determining not only which features are important to the model, but how important a feature is for a particular classification given its value. Lastly, we use decision boundaries from the model to revise an already existing method of classification, essentially asking the tree-based method where decision boundaries are best placed and defining a new classification method. We showcase these techniques by applying them to the problem of star-galaxy separation using data from the Sloan Digital Sky Survey (hereafter SDSS). We use the output of MINT and the ensemble methods to demonstrate how more complex decision boundaries improve star-galaxy classification accuracy over the standard SDSS frames approach (reducing misclassifications by up to ${≈ }33{{\ \rm per\ cent}}$ ).